Relation between wall shear stress and carotid artery wall thickening MRI versus CFD. Issue 5 (21st March 2016) - Cibis, Merih; Potters, Wouter V.; Selwaness, Mariana; Gijsen, Frank J.; Franco, Oscar H.; Arias Lorza, Andres M.; de Bruijne, Marleen; Hofman, Albert; van der Lugt, Aad; Nederveen, Aart J.; Wentzel, Jolanda J.
Abstract: Wall shear stress (WSS), a parameter associated with endothelial function, is calculated by computational fluid dynamics (CFD) or phase-contrast (PC) MRI measurements. Although CFD is common in WSS (WSSCFD ) calculations, PC-MRI-based WSS (WSSMRI ) is more favorable in population studies; since it is straightforward and less time consuming. However, it is not clear if WSSMRI and WSSCFD show similar associations with vascular pathology. Our aim was to test the associations between wall thickness (WT) of the carotid arteries and WSSMRI and WSSCFD . The subjects ( n =14) with an asymptomatic carotid plaque who underwent MRI scans two times within 4 years of time were selected from the Rotterdam Study. We compared WSSCFD and WSSMRI at baseline and follow-up. Baseline WSSMRI and WSSCFD values were divided into 3 categories representing low, medium and high WSS tertiles. WT of each tertile was compared by a one-way ANOVA test. The WSSMRI and WSSCFD were 0.50±0.13 Pa and 0.73±0.25 Pa at baseline. Although WSSMRI was underestimated, a significant regression was found between WSSMRI and WSSCFD ( r 2 =0.71). No significant difference was found between baseline and follow-up WSS by CFD and MRI-based calculations. The WT at baseline was 1.36±0.16 mm and did not change over time. The WT was 1.55±0.21 mm in low, 1.33±0.20 mm in medium and 1.21±0.21 mm in the high WSSMRI tertiles. Similarly, the WT was 1.49±0.21 mm in low, 1.33±0.20 mm in medium and 1.26±0.21 mm in high WSSCFD tertiles. We found that WSSMRI and WSSCFD were inversely related with WT. WSSMRI and WSSCFD patterns were similar although MRI-based calculations underestimated WSS.